Growth and yield of bok choy (Brassica rapa L.) plants in post-rock excavation soils provided with phosphate-solubilizing bacteria and manure - Hidayat, Cecep; Rachmawati, Yati Setiati; Utami, Dhea Rizqi; Hasani, Sofiya; Roosda, Anna Aina; Chandria, Windhy (Universitas Padjadjaran, 2024)
Elevated sand and gravel mining to meet market needs causes negative impacts on the environment, soil, and biodiversity. The government issued a regulation that requires revegetation as reclamation of mineral and coal mining. The conversion needs to overcome the physical and chemical characteristics of post-rock excavation soil that can be utilized by economic value plants such as bok choy. This experiment aimed to determine the growth and yield of bok choy on post-rock excavation soil by providing phosphate solubilizing bacteria (PSB) and various manure types. The study was conducted in Margasari Village, Buah Batu District, Bandung at an altitude of 671 m above sea level and at the Soil Biotechnology Laboratory, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung from April to June 2023. The experimental design used was a factorial Randomized Block Design (RBD) with two factors and repeated three times. The first factor was PSB isolate dose (without PSB; 5 mL polybag-1; 10 mL polybag-1; 15 mL polybag-1, and 20 mL polybag-1). The second factor was manure variety (cow, goat, and laying hen manure, each of 15 t ha-1). The parameters observed comprised the soil and plant parameters. The results showed that there was no interaction between the dose of PSB isolate and various types of manure on the growth and yield of bok choy plants. The PSB isolate and manure had not been able yet to increase the growth and yield of Bok Choy (Brassica rapa L.) plants on post-rock excavation soil, mainly due to the soil nature.